PROSPEK PROBIOTIK DALAM PENCEGAHAN AGRESIVITAS RESORBSI OSTEOKLASTIK TULANG ALVEOLAR YANG DIINDUKSI LIPOPOLISAKARIDA PADA PENYAKIT PERIODONTAL: PROBIOTIC PROSPECT IN THE PREVENTION OF AGGRESSIVENESS OSTEOCLASTIC ALVEOLAR BONE RESORPTION INDUCED BY LIPOPOLYSACCHARIDE ON PERIODONTAL DISEASE - Muhammad Nurul Amin; Zahara Meilawaty; Desi Sandrasari (Dentika: Dental Journal, 2010)
This study was an experimental laboratory. The purpose of this study was to determine the role of probiotics in inhibitingthe activity of pathogenic bacterial oral cavity. The result of study is expected to be used for prevention and treatment ofperiodontal disease which is still complex and derived products with high quality probiotics. The main product is thedevelopment potential of probiotics in maintaining oral health, especially periodontal disease is effectively and efficiently.This study used rats and divided into 4 groups: Group I, control without treatment; group II, induction of LPS E. coli for 5days, Group III, LPS induction of E. coli + Probiotic Bacterial Lactobacillus casei injection for 5 days together, and groupIV, induction of LPS E. coli for 5 days + 5 days injection of Lactobacillus casei. Immunohistochemical examination wasdone to evaluate the activity of osteoclasts in alveolar bone resorption to detect TRAP (tartarate-resistant acidphosphatase) and Carboxyterminal Telopeptide of Type 1 Collagen (1CTP) and subsequently analyzed the data collectedstatistically. The results of this study showed that induction of LPS could trigger the occurrence of alveolar boneresorption mediated by osteoclast and Lactobacillus casei administration both at the same time with the LPS induction orafter LPS induction can inhibit osteoclastic alveolar bone resorption. In conclusion, clinically it can be interpreted that theadministration of probiotic can be given at the beginning of periodontal disease occurs before or at the time of periodontaldisease is underway.